Fostering Active Learning and Writing Proficiency: The Role of Contextual Teaching and Learning Approach in EFL Descriptive Texts - Armita Permatasari (Jurnal Ilmiah Multidisiplin, 2025)
This study aimed at finding out the impact of Contextual Teaching and Learning Approach in enhancing EFL learners descriptive text writing skill and also perception of learners about the utilization of Contextual Teaching and Learning Approach in writing descriptive text. This study employed experimental research which the experimental group was given treatment using CTL Approach, on the other hand, the control group was given treatment using the conventional way. The participants were forty-eight of the first semester learners of Agricultural faculty at Universitas Muhammadiyah Sinjai, in 2024-2025 academic year. Two intact classes were randomly selected as control and experimental group and each group comprised twenty-four learners. The research instrument that was used in this study were pre-posttest and the perceptional questionnaires. The data were analyzed by using descriptive statistics and inferential statistics on SPSS. The result of this study showed that the significance value (Sig.) in the table is 0.007, which is less than 0.05. Therefore, there was a significant difference between learners who was taught by using CTL approach and those were taught by using conventional teaching. Then, learners responded positively to the implementation of CTL Approach. So that, further researches with deepest investigation to examine follow-up activities after knowing student perceptions are highly recommended.